Assessment of 25(OH)D vitamin concentration in plasma of residents of Lodz with metabolic syndrome in pre- and postmenopausal period - Godala, Małgorzata; Materek-Kuśmierkiewicz, Izabela; Moczulski, Dariusz; Gaszyńska, Ewelina; Szatko, Franciszek; Tokarski, Sławomir; Kowalski, Jan (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: Vitamin D deficiency is a risk factor for metabolic syndrome disorders and the occurrence of these disorders greatly contributes to the deficiency of vitamin D. Postmenopausal women are particularly prone to that deficiency. Aim : The aim of the study was to assess vitamin D concentration in the plasma of pre- and postmenopausal women, with or without metabolic syndrome. Material and methods : The study included 141 women aged 26-77 (the mean age 58.74 years old), divided into 4 groups depending on the pre- or postmenopausal period and diagnosed or not with metabolic syndrome according to the International Diabetes Federation criteria (2005). Vitamin D concentration was assessed by LIAISON® test using chemiluminescent immunoassay (CLIA) technology. Results: The mean vitamin D concentration was the highest among premenopausal women without metabolic syndrome (24.32 ng/ml), it was insignificantly higher than in postmenopausal women without metabolic syndrome (23.52 ng/ml) and significantly higher than in both groups with metabolic syndrome – premenopausal (19.86 ng/ml) and postmenopausal women (9.32 ng/ml). The recommended plasma 25(OH)D concentration was not found in any of postmenopausal women with diagnosed metabolic syndrome. Conclusions : Postmenopausal women with metabolic syndrome had a significantly lower 25(OH)D vitamin concentration in plasma than postmenopausal women without metabolic syndrome. The frequency of vitamin D deficiency in women with metabolic syndrome was very high, significantly higher than in women without metabolic syndrome.